Digitalizing firms: Skills, work organization and the adoption of new enabling technologies - Valeria Cirillo; Lucrezia Fanti; Andrea Mina; Anrea Ricci (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2021)
New enabling technologies are shaping the transformation of production activities. This process of change is characterised by growing digitization, inter-connectivity and automation. The diffusion of new technologies is, however, very uneven, and firms display different adoption behaviours. By using panel data on a large representative sample of Italian firms, we explore the patterns and determinants of new digital technology adoption. We build our theoretical framework on the nexus between technology, skills and the organisation of work. We then provide novel econometric evidence on the positive effects of human capital and training. Among the notable results of the paper, labour flexibility does not seem to favour new technology adoption, whereas second-level collective bargaining plays a positive role in the process. Results also show heterogeneous effects between large vs. small and medium-size firms, and between manufacturing and service sectors.
Keywords: D20; L23; O33; 330; Digital technologies; Industry 4.0; skills; human capital; work organisation